The role of governance in raising the level of financial disclosure and its impact on the quality and integrity of financial reports (Field study 2023-2024) - Al-Balawi, Hind Mansour (Journal of Economic, Administrative and Legal Sciences, 2025)
Governance is a fundamental concept that influences financial transparency within organizations. This study, conducted between 2023 and 2024, aims to analyze the impact of governance mechanisms on financial transparency and the quality and integrity of financial reports. It also highlights the effects of governance structures, including board composition, audit committees, and internal control systems, on financial transparency. To achieve this, the study relied on a quantitative statistical methodology based on field questionnaires. These questionnaires were administered to a stratified random sample of 97 participants among employees of listed companies on the stock exchange. By applying statistical analysis to data collected using SPSS, the study finds a strong positive correlation between effective governance practices and financial disclosure levels. The results indicated that 71.1% of the participants agree that a strong governance structure contributes to transparent financial disclosure, while 91.7% confirmed that good governance practices enhance the accuracy of financial reports. The findings also demonstrated that governance mechanisms reduce financial fraud by 87.7%. Additionally, the results underscore the importance of ongoing monitoring and evaluation of governance frameworks to ensure the reliability and credibility of financial reporting.
Keywords: Governance mechanisms; Financial transparency; Financial disclosure; Reporting accuracy; Integrity of financial reports